Effect Size Pengaruh Model Pembelajaran SETS terhadap Keterampilan Berpikir Abad-21 Siswa dalam Pembelajaran Fisika - Nuril Huda; Tomi Apra Santosa; Abdul Rahman; Yayat Suharyat; Ilwandri Ilwandri; Ichsan Ichsan; Yayan Oktiawan (Pendidikan Fisika Universitas Nurul Huda, 2023)
This study aims to determine the effect of the SETS learning model on students' 21st century thinking skills in physics learning. This type of research is a meta-analysis study. The population in this study came from elementary school (SD), junior high school (SMP) and high school (SMA) level students in Indonesia. The research samples came from 11 national and international journals that have been published from 2018-2023. Data source searches come from google scholar, sciencedirect, eric and proquest. Data collection techniques in the form of direct observation through online databases. The results showed that the average value of Effect Size (ES = 0.82) with high criteria. This finding shows that the science environment, technology and society (SETS) learning model has a huge influence on students' 21st century skills in physics learning, this SETS learning model helps teachers in encouraging students' 21st century thinking skills in learning